Determinação do ponto de fulgor e pressão de vapor Reid em petróleo por HTGC e DHA associados à quimiometria - Nascimento, Márcia Helena Cassago (2018)
Flash Point (FP) and Reid vapor pressure (RVP) are important physico-chemical properties of petroleum, used as safety parameters and environment. The essayfor the measurement of FP and RVP are carried out in crude oil and in some fractions, providing thequality parameters of oil and derivatives. It was proposed in this work, an innovative methodology for determining the FP and RVP in crude oil, using the high temperature gas chromatography (HTGC) and detailed hydrocarbon analysis (DHA), associated with regression by the minimum partial squares (PLS). The HTGC is usually used for the simulated distillation of oil. However,there is a limitation on this technique in the initial part of the curve, light-end, equivalent to distillation until nC10. The DHA technique provides elution of the lighter oil components, therefore, the information of these techniques is of the complementary character. For this work, 128 samples of crude oil (with API density between 17.0 to 54.0) were used, from the Brazilian sedimentary basin. For the determination of the physico-chemical properties, FP and RVP, of crude oil, by means of these chromatographic techniques,was heldthe association of thesedata with themultivariate calibration,by PLS. A high-level data fusion was applied to the data chromatographic of the techniques DHA and HTGC in the determination of FP and RVP. To better describe the TBP curve, the composition of a medium-level data fusion was applied between the simulated curves, by the two techniques, to generate a complete TBP curve by simulated distillation. Due to the direct relationship with the volatile constituents in petroleum, it was possible to effectively predict these two properties from the chromatographic data of the HTGC and DHA techniques. The main result was obtained by means of the chromatograms of HTGC in determining the Reid vapor pressure, with average error (RMSEP) of 0.4 kPa and coefficient of determination (R2p) of 0.99. With the fusion of information of the two chromatographic techniques it was possible to estimate the flash point with average error of 5.3 ºC and coefficient of determination of 0.89. Data fusion represents information gain in the flash point estimation, however, to estimate the Reid vapor pressure, the chromatograms by HTGC are sufficient. The models developed were statistically evaluated as to the presence of errors in the residues. Test F was applied to evaluate the improvement in accuracy by the data fusion, while the statistical significance was evaluated by the permutationtest of the property values of reference. The models were also evaluated by the chemical significance. The Results they point to chemically and statistically significant models. In addition, a data merger provided significant improvement in the TBP curve simulated bytheHTGC, with greater scope of information ofthelight hydrocarbons. The provision of the TBP curve with more information and the determination of the properties by means of the chromatographic data with chemometrics, have been satisfactorily completed